Bonding wire for semiconductor devices

By forming a Pd coating on the Cu alloy core material and adding specific elements to its surface, the ball joint life of the Cu bonding wire in a high temperature and high humidity environment is improved, and the problem of insufficient bonding reliability of the existing Cu bonding wire is solved.

CN112038313BActive Publication Date: 2025-02-28NIPPON STEEL CHEM & MATERIAL CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202010956086.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2015-06-05
Filing Date
2015-09-18
Publication Date
2025-02-28
Estimated Expiration
2035-09-18

Smart Images

  • Figure BDA0002678636480000191
    Figure BDA0002678636480000191
  • Figure BDA0002678636480000201
    Figure BDA0002678636480000201
  • Figure BDA0002678636480000211
    Figure BDA0002678636480000211
Patent Text Reader

Abstract

Provided is a bonding wire, which is a Cu bonding wire having a Pd coating layer on the surface, which improves the bonding reliability of the ball joint in a high temperature and high humidity environment and is suitable for vehicle-mounted equipment. A bonding wire for a semiconductor device has a Cu alloy core and a Pd coating layer formed on the surface thereof, and the bonding wire contains a total of 0.1 to 100 mass ppm of one or more elements of As, Te, Sn, Sb, Bi, and Se. As a result, the bonding life of the ball joint in a high temperature and high humidity environment can be increased and the bonding reliability can be improved. When the Cu alloy core also contains 0.011 to 1.2 mass % of one or more of Ni, Zn, Rh, In, Ir, Pt, Ga, and Ge, respectively, the reliability of the ball joint in a high temperature environment of 170°C or above can be improved. In addition, when an alloy skin layer containing Au and Pd is further formed on the surface of the Pd coating layer, the wedge bonding property is improved.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application is a divisional application of a Chinese patent application with an application date of September 18, 2015, application number 201580002533.6, and invention name “Bonding Wire for Semiconductor Device”. Technical Field

[0002] The present invention relates to a bonding wire for a semiconductor device used to connect electrodes on a semiconductor element and wiring on a circuit wiring board such as an external lead. Background Art

[0003] At present, as a bonding wire for semiconductor devices that connects the electrode on the semiconductor element to the external lead (hereinafter referred to as bonding wire), a thin wire with a wire diameter of about 15 to 50 μm is mainly used. The bonding method of the bonding wire is generally a thermal compression method using ultrasonic waves, and a general bonding device and a capillary tool that passes the bonding wire inside for connection can be used. The bonding process of the bonding wire is completed by the following process: the tip of the wire is heated and melted by arc heat input, and a ball (FAB: Free Air Ball, airless ball) is formed by surface tension, and the ball is pressed and bonded to the electrode of the semiconductor element heated in the range of 150°C to 300°C (hereinafter referred to as ball bonding), and then, after forming a loop, the wire is pressed and bonded to the electrode on the external lead side (hereinafter referred to as wedge bonding). The electrode on the semiconductor element to be bonded by the bonding wire can be an electrode structure in which an alloy film mainly composed of Al is formed on a Si substrate, and the electrode on the external lead side can be an electrode structure with a Ag plated layer or a Pd plated layer applied.

[0004] Au has been the mainstream material for bonding wires so far, but work is progressing to replace it with Cu, mainly for LSI applications. On the other hand, with the popularity of electric vehicles and hybrid vehicles in recent years, the demand for replacing Au with Cu in vehicle-mounted device applications is also increasing.

[0005] Regarding Cu bonding wire, a Cu bonding wire using high-purity Cu (purity: 99.99 mass % or more) has been proposed (for example, Patent Document 1). Cu has the disadvantage of being easily oxidized compared to Au, and has problems such as poor bonding reliability, ball forming properties, and wedge bonding properties. As a method for preventing surface oxidation of Cu bonding wire, a structure in which the surface of a Cu core material is coated with a metal such as Au, Ag, Pt, Pd, Ni, Co, Cr, and Ti has been proposed (Patent Document 2). In addition, a structure in which the surface of a Cu core material is coated with Pd and then the surface is coated with Au, Ag, Cu, or an alloy thereof has been proposed (Patent Document 3).

[0006] Prior Art Literature

[0007] Patent Literature

[0008] Patent Document 1: Japanese Patent Application Laid-Open No. 61-48543

[0009] Patent Document 2: Japanese Patent Application Publication No. 2005-167020

[0010] Patent Document 3: Japanese Patent Application Publication No. 2012-36490 Summary of the invention

[0011] Compared with general electronic equipment, vehicle-mounted equipment requires higher joint reliability in harsh high-temperature and high-humidity environments. In particular, the joint life of the ball joint that joins the ball part of the wire to the electrode has become the biggest problem. Several methods for evaluating the joint reliability in high-temperature and high-humidity environments have been proposed. As a representative evaluation method, there is HAST (Highly Accelerated Temperature and Humidity Stress Test). When HAST is used to evaluate the joint reliability of the ball joint, the ball joint used for evaluation is exposed to a high-temperature and high-humidity environment with a temperature of 130°C and a relative humidity of 85%, and the time-dependent change in the resistance value of the joint or the time-dependent change in the shear strength of the ball joint is measured to evaluate the joint life of the ball joint. Recently, a joint life of more than 100 hours has begun to be required in HAST under such conditions.

[0012] The conventional Cu bonding wire with a Pd coating was used to bond to a pure Al electrode. The 1st bonding was a ball bonding and the 2nd bonding was a wedge bonding. After being encapsulated with epoxy resin, the above-mentioned HAST conditions were evaluated. The results showed that the bonding life of the ball bonding part was sometimes less than 100 hours, and the bonding reliability required for vehicle-mounted equipment was insufficient.

[0013] An object of the present invention is to provide a bonding wire which is a Cu bonding wire having a Pd coating layer on the surface, which improves the bonding reliability of a ball joint in a high-temperature and high-humidity environment and is suitable for vehicle-mounted equipment.

[0014] That is, the gist of the present invention is as follows.

[0015] (1) A bonding wire for a semiconductor device, comprising a Cu alloy core material and a Pd coating layer formed on a surface of the Cu alloy core material, wherein:

[0016] The bonding wire contains at least one element selected from As, Te, Sn, Sb, Bi, and Se, and the total concentration of the elements is 0.1 to 100 mass ppm relative to the entire wire, with Sn ≤ 10 mass ppm, Sb ≤ 10 mass ppm, and Bi ≤ 1 mass ppm.

[0017] (2) The bonding wire for a semiconductor device according to (1) above, wherein the total concentration of at least one element selected from As, Te, Sn, Sb, Bi, and Se is 1 to 100 mass ppm relative to the entire wire.

[0018] (3) The bonding wire for a semiconductor device according to (1) or (2) above, wherein the thickness of the Pd coating layer is 0.015 to 0.150 μm.

[0019] (4) The semiconductor device bonding wire according to any one of (1) to (3) above, further comprising an alloy skin layer containing Au and Pd on the Pd coating layer.

[0020] (5) The bonding wire for a semiconductor device according to (4) above, wherein the thickness of the alloy skin layer containing Au and Pd is 0.0005 to 0.050 μm.

[0021] (6) The bonding wire for a semiconductor device according to any one of (1) to (5) above, characterized in that the bonding wire further contains at least one element selected from Ni, Zn, Rh, In, Ir, Pt, Ga, and Ge, and the concentration of the element is 0.011 to 1.2 mass % relative to the entire wire.

[0022] (7) The bonding wire for a semiconductor device according to any one of (1) to (6) above, wherein the Cu alloy core material contains Pd, and the concentration of Pd contained in the Cu alloy core material is 0.05 to 1.2 mass %.

[0023] (8) The bonding wire for a semiconductor device according to any one of (1) to (7) above, wherein the bonding wire further contains at least one element selected from B, P, Mg, Ca, and La, and the concentration of the element is 1 to 100 ppm by mass relative to the entire wire.

[0024] (9) A bonding wire for a semiconductor device according to any one of (1) to (8) above, characterized in that, in a measurement result of the crystal orientation on the surface of the bonding wire, the existence ratio of the crystal orientation <111> having an angle difference of 15 degrees or less relative to the longitudinal direction of the bonding wire is 30 to 100% in terms of area ratio.

[0025] (10) The bonding wire for a semiconductor device according to any one of (1) to (9) above, wherein Cu exists on the outermost surface of the bonding wire.

[0026] According to the present invention, for a bonding wire for a semiconductor device having a Cu alloy core and a Pd coating layer formed on the surface of the Cu alloy core, the bonding wire contains a total of 0.1 to 100 mass ppm of at least one element selected from As, Te, Sn, Sb, Bi, and Se, thereby increasing the bonding life of the ball joint in a high temperature and high humidity environment and improving the bonding reliability. DETAILED DESCRIPTION

[0027] The bonding wire of the present invention comprises a Cu alloy core material and a Pd coating layer formed on the surface of the Cu alloy core material, and the bonding wire contains a total of 0.1 to 100 mass ppm of at least one element selected from As, Te, Sn, Sb, Bi, and Se. The bonding wire of the present invention having this specific structure can improve the bonding reliability of the ball joint under the high temperature and high humidity environment required for vehicle-mounted equipment.

[0028] The details will be described later. If the bonding wire of the present invention is used to form a ball by arc discharge, an alloy layer having a higher Pd concentration than the inside of the ball is formed on the surface of the ball during the melting and solidification of the bonding wire. If the ball is bonded to an Al electrode and a high temperature and high humidity test is performed, Pd is concentrated at the bonding interface. The concentrated layer formed by the Pd concentration can inhibit the diffusion of Cu and Al at the bonding interface in the high temperature and high humidity test, reduce the growth rate of easily corrosive compounds, and significantly improve the bonding reliability of the ball bonding portion in a high temperature and high humidity environment.

[0029] In addition, the alloy layer with a high Pd concentration formed on the ball surface has excellent oxidation resistance, and thus it is possible to reduce defects such as the formation position of the ball being offset from the center of the bonding wire when forming the ball.

[0030] From the viewpoint of increasing the bonding life of the ball joint in a high temperature and high humidity environment of 130°C and 85% relative humidity and improving the bonding reliability, the total concentration of at least one element selected from As, Te, Sn, Sb, Bi, and Se relative to the entire bonding wire is 0.1 mass ppm or more, preferably 0.5 mass ppm or more, more preferably 1 mass ppm or more, and further preferably 1.5 mass ppm or more, 2 mass ppm or more, 2.5 mass ppm or more, or 3 mass ppm or more.

[0031] The mold resin (epoxy resin) used as the shell of the semiconductor device contains chlorine (Cl) in the molecular skeleton. Under the HAST evaluation conditions, i.e., 130°C and 85% relative humidity, the Cl in the molecular skeleton is hydrolyzed to form chloride ions (Cl -) is dissolved (eluted) in the form of. In the case where a Cu bonding wire without a coating layer is bonded to an Al electrode, if the Cu / Al bonding interface is placed at a high temperature, Cu and Al diffuse into each other and eventually form an intermetallic compound Cu9Al4. Cu9Al4 is easily corroded by halogens and corrodes due to chlorides dissolved from the mold resin, resulting in reduced bonding reliability. In the case where the Cu wire has a Pd coating layer, the bonding interface between the Pd-coated Cu wire and the Al electrode becomes a structure such as Cu / Pd concentrated layer / Al. Although the formation of the Cu9Al4 intermetallic compound is suppressed compared to the Cu wire without a coating layer, the bonding reliability in the high temperature and high humidity environment required for vehicle-mounted equipment is insufficient.

[0032] In contrast, it is believed that if the Cu bonding wire coated with Pd as in the present invention contains a specified amount of at least one element selected from As, Te, Sn, Sb, Bi, and Se, the formation of Cu9Al4 intermetallic compounds in the joint portion tends to be further suppressed. If a specified amount of these elements is contained, when forming a ball, the interfacial tension between the Cu of the core material and the Pd of the coating layer is reduced, and the wettability of the interface is optimized, thereby more significantly showing the Pd concentration at the ball joint interface. Therefore, the effect of suppressing the mutual diffusion of Cu and Al brought by the Pd concentrated layer is further enhanced, and it is speculated that the generation of Cu9Al4, which is easily corroded by the action of Cl, is reduced, and the bonding reliability of the ball joint in the high temperature and high humidity environment is particularly improved.

[0033] In the present invention having a Cu alloy core material and a Pd coating layer formed on the surface of the Cu alloy core material, and further having a skin alloy layer containing Au and Pd on the surface of the Pd coating layer as required, if diffusion heat treatment and annealing heat treatment are performed as described later, the Cu of the core material diffuses in the coating layer and the skin alloy layer by grain boundary diffusion, etc., and Cu can reach the outermost surface of the wire and exist on the outermost surface. Therefore, in the present invention, Cu may exist on the outermost surface of the bonding wire.

[0034] In the case where the Pd-coated Cu bonding wire contains a specified amount of As, Te, Sn, Sb, Bi, and Se as in the present invention, if Cu is further present on the outermost surface of the bonding wire, there is a tendency that the generation of Cu9Al4 intermetallic compounds in the bonding portion is further suppressed. In the case where the Pd-coated Cu bonding wire contains a specified amount of As, Te, Sn, Sb, Bi, and Se, if Cu is further present on the outermost surface of the bonding wire, the interaction between As, Te, Sn, Sb, Bi, and Se contained in the bonding wire and Cu promotes the concentration of Pd on the FAB surface during FAB formation, and the concentration of Pd at the ball bonding interface is more significantly manifested. As a result, it is presumed that the effect of suppressing the mutual diffusion of Cu and Al brought about by the Pd concentration layer is further enhanced, the generation amount of Cu9Al4 that is easily corroded due to the action of Cl is reduced, and the bonding reliability of the ball bonding portion in a high temperature and high humidity environment is further improved.

[0035] When measuring the surface of the bonding wire using an Auger electron spectroscopy device, if Cu is detected on the surface, it can be said that Cu exists on the outermost surface, and the above-mentioned effect can be exerted. Furthermore, if the Cu concentration is 1 atomic % or more relative to the metal element constituting the outermost surface of the bonding wire, the effect of improving the bonding reliability of the ball joint under the high temperature and high humidity environment can be more effectively manifested, and thus it is preferred. From the viewpoint of further improving the bonding reliability of the ball joint under the high temperature and high humidity environment, the Cu concentration is more preferably 1.5 atomic % or more, and more preferably 2 atomic % or more, 2.5 atomic % or more, or 3 atomic % or more relative to the metal element constituting the outermost surface of the bonding wire. In addition, from the viewpoint of suppressing the reduction of the oxidation resistance and sulfurization resistance of the wire surface and suppressing the reduction of the service life of the bonding wire, the Cu concentration is preferably 50 atomic % or less, more preferably 45 atomic % or less, and more preferably 40 atomic % or less, 35 atomic % or less, or 30 atomic % or less relative to the metal element constituting the outermost surface of the bonding wire.

[0036] Furthermore, there is a tendency that the above-mentioned effect due to the presence of Cu on the surface is exhibited when the purity of Cu in the core material is low (for example, 3N or less), and is particularly more prominently exhibited when the purity of Cu is 2N or less.

[0037] The effect of improving the bonding reliability of the ball joint in a high temperature and high humidity environment due to the presence of Cu on the outermost surface of the bonding wire is unique to the bonding wire of the present invention containing specified amounts of As, Te, Sn, Sb, Bi, and Se. In a general Pd-coated Cu bonding wire that does not contain these elements, the bonding reliability of the ball joint in a high temperature and high humidity environment cannot be improved as in the present invention. In addition, the general Pd-coated Cu bonding wire that does not contain these elements has Cu on the outermost surface of the bonding wire, which reduces the oxidation resistance and sulfurization resistance of the wire surface, and reduces the service life of the bonding wire. In addition, the FAB is more likely to be eccentric, and the ball shape is easily deteriorated. In addition, a tendency for the wedge bondability to deteriorate is observed.

[0038] The above-mentioned effect due to the presence of Cu on the outermost surface of the bonding wire is exhibited in the bonding wire of the present invention in the same manner when the Pd coating layer is the outermost surface and when the alloy skin layer containing Au and Pd is the outermost surface.

[0039] Here, the outermost surface refers to a region on the bonding wire surface measured by an Auger electron spectrometer in a state where sputtering or the like is not performed.

[0040] On the other hand, from the viewpoint of obtaining a good FAB shape and thus good ball bonding, the total concentration of the above elements in the wire is 100 mass ppm or less, preferably 95 mass ppm or less, 90 mass ppm or less, 85 mass ppm or less, or 80 mass ppm or less. In addition, when the concentration of Sn or Sb exceeds 10 mass ppm, or when the concentration of Bi exceeds 1 mass ppm, the FAB shape becomes poor, so it is preferred to set Sn≤10 mass ppm, Sb≤10 mass ppm, and Bi≤1 mass ppm, because the FAB shape can be further improved. Furthermore, it is more preferred to set the Se concentration to 4.9 mass ppm or less, because the FAB shape and wedge bonding can be further improved.

[0041] When As, Te, Sn, Sb, Bi, and Se are contained in the bonding wire, the effect of the present invention can be exerted regardless of whether the method of containing these elements in the Cu core material or the method of containing these elements by coating the Cu core material or the wire surface is adopted. Since the amount of these components added is extremely small, the variation of the addition method is wide, and the effect can be exerted regardless of the method of addition, as long as the components are contained in the specified concentration range.

[0042] In the bonding wire of the present invention, from the viewpoint of further improving the bonding reliability of the ball joint under the high temperature and high humidity environment required for vehicle-mounted equipment, the thickness of the Pd coating layer is preferably 0.015 μm or more, more preferably 0.02 μm or more, further preferably 0.025 μm or more, 0.03 μm or more, 0.035 μm or more, 0.04 μm or more, 0.045 μm or more, or 0.05 μm or more. On the other hand, from the viewpoint of obtaining a good FAB shape, the thickness of the Pd coating layer is preferably 0.150 μm or less, more preferably 0.140 μm or less, 0.130 μm or less, 0.120 μm or less, 0.110 μm or less, or 0.100 μm or less.

[0043] The definitions of the Cu alloy core and the Pd coating layer of the above-mentioned bonding wire are explained. The boundary between the Cu alloy core and the Pd coating layer is determined based on the Pd concentration. The position where the Pd concentration is 50 atomic % is used as the boundary, the area where the Pd concentration is 50 atomic % or more is determined as the Pd coating layer, and the area where the Pd concentration is less than 50 atomic % is determined as the Cu alloy core. The reason for this is that if the Pd concentration in the Pd coating layer is 50 atomic % or more, the improvement effect of the characteristics can be obtained by the structure of the Pd coating layer. The Pd coating layer may include an area of ​​a layer consisting only of Pd, and an area where Pd and Cu have a concentration gradient in the depth direction of the wire. In the Pd coating layer, the reason for the formation of the area with the concentration gradient is that sometimes the atoms of Pd and Cu diffuse through heat treatment in the manufacturing process. In the present invention, the concentration gradient refers to the degree of concentration change in the depth direction of 10 mol% or more per 0.1 μm. Furthermore, the Pd coating layer may contain unavoidable impurities.

[0044] The bonding wire of the present invention may further include an alloy skin layer containing Au and Pd on the surface of the Pd coating layer. Thus, the bonding wire of the present invention can further improve bonding reliability and wedge bonding properties.

[0045] The definition of the alloy skin layer containing Au and Pd of the above-mentioned bonding wire is explained. The boundary between the alloy skin layer containing Au and Pd and the Pd coating layer is determined based on the Au concentration. The position where the Au concentration is 10 atomic % is used as the boundary, and the area where the Au concentration is more than 10 atomic % is determined as the alloy skin layer containing Au and Pd, and the area where the Au concentration is less than 10 atomic % is determined as the Pd coating layer. In addition, even if the Pd concentration is more than 50 atomic %, as long as there is 10 atomic % of Au, it is determined to be an alloy skin layer containing Au and Pd. The reason is that if the Au concentration is in the above-mentioned concentration range, the improvement effect of the characteristics can be expected from the structure of the Au skin layer. The alloy skin layer containing Au and Pd is an Au-Pd alloy, including two cases: a case where Au and Pd have a concentration gradient in the depth direction of the wire, and a case where the area having the concentration gradient is not included. The alloy skin layer containing Au and Pd preferably includes an area having the concentration gradient. The reason why the region having the concentration gradient is formed in the alloy skin layer containing Au and Pd is due to the diffusion of Au and Pd atoms by heat treatment in the manufacturing process, etc. Furthermore, the alloy skin layer containing Au and Pd may contain unavoidable impurities and Cu.

[0046] In the bonding wire of the present invention, the alloy skin layer comprising Au and Pd can react with the Pd coating layer to improve the adhesion strength between the alloy skin layer comprising Au and Pd, the Pd coating layer, and the Cu alloy core material, and suppress the peeling of the Pd coating layer and the alloy skin layer comprising Au and Pd during wedge bonding. As a result, the bonding wire of the present invention can improve wedge bonding. From the viewpoint of obtaining good wedge bonding, the thickness of the alloy skin layer comprising Au and Pd is preferably 0.0005 μm or more, more preferably 0.001 μm or more, 0.002 μm or more, or 0.003 μm or more. From the viewpoint of suppressing eccentricity and obtaining a good FAB shape, the thickness of the alloy skin layer comprising Au and Pd is preferably 0.050 μm or less, more preferably 0.045 μm or less, 0.040 μm or less, 0.035 μm or less, or 0.030 μm or less. The alloy skin layer composed of Au and Pd can be formed by the same method as the method for forming the Pd coating layer.

[0047] The mold resin (epoxy resin) that serves as the outer shell of the semiconductor device contains a silane coupling agent. The silane coupling agent has the function of improving the adhesion between organic matter (resin) and inorganic matter (silicon, metal), and thus can improve the adhesion with the silicon substrate and metal. Furthermore, in the case of semiconductors for vehicles that require reliability at higher temperatures and require high adhesion, a "sulfur-containing silane coupling agent" is added. The sulfur contained in the mold resin will not be liberated under the temperature condition of HAST, that is, around 130°C, but will be liberated if used under conditions above 175°C (for example, 175°C to 200°C). Moreover, if the sulfur liberated at a high temperature above 175°C comes into contact with Cu, the corrosion of Cu becomes severe, generating sulfide (Cu2S) and oxide (CuO). If corrosion of Cu occurs in a semiconductor device using Cu bonding wire, the bonding reliability of the ball bonding part in particular will be reduced.

[0048] As a method for evaluating the bonding reliability of ball joints in a high temperature environment above 170°C, HTS (High Temperature Storage Test) can be used. For samples for evaluation exposed to a high temperature environment, the change in the resistance value of the ball joint over time, or the change in the shear strength of the ball joint over time, is measured to evaluate the bonding life of the ball joint. In recent years, in semiconductor devices for automotive use, there is a demand for improved bonding reliability of ball joints in HTS at 175°C to 200°C.

[0049] Preferably, the bonding wire of the present invention further contains at least one element selected from Ni, Zn, Rh, In, Ir, Pt, Ga, and Ge, and the concentration of the elements is 0.011 to 1.2 mass % relative to the entire wire. The bonding wire of the present invention further contains these elements, and the performance in HTS of 175°C or above is improved among the bonding reliability of the ball joint in a high temperature environment. From the viewpoint of improving the bonding reliability of the ball joint in a high temperature environment (particularly the performance in HTS of 175°C or above), the concentration of the elements is preferably 0.011 mass % or more, more preferably 0.020 mass % or more, and further preferably 0.030 mass % or more, 0.050 mass % or more, 0.070 mass % or more, 0.090 mass % or more, 0.10 mass % or more, 0.15 mass % or more, or 0.20 mass % or more relative to the entire wire. From the viewpoint of obtaining a good FAB shape, suppressing the hardening of the bonding wire, and suppressing the reduction of the wedge bonding property, the concentration of the above elements is preferably 1.2% by mass or less, and more preferably 1.1% by mass or less, relative to the entire wire. In the case where the bonding wire of the present invention contains a plurality of elements selected from Ni, Zn, Rh, In, Ir, Pt, Ga, and Ge, the total concentration of these elements is preferably 0.011 to 2.2% by mass relative to the entire wire. From the viewpoint of improving the bonding reliability of the ball joint in a high temperature environment (particularly the performance in HTS above 175°C), the total concentration of the above elements is preferably 0.011% by mass or more, more preferably 0.020% by mass or more, and further preferably 0.030% by mass or more, 0.050% by mass or more, 0.070% by mass or more, 0.090% by mass or more, 0.10% by mass or more, 0.15% by mass or more, or 0.20% by mass or more. From the viewpoint of obtaining a good FAB shape, suppressing hardening of the bonding wire, and suppressing reduction in wedge bondability, the total concentration of the elements is preferably 2.0 mass % or less, 1.8 mass % or less, or 1.6 mass % or less relative to the entire wire.

[0050] In addition, it is preferred that: in the bonding wire of the present invention, the Cu alloy core material contains Pd, and the concentration of Pd contained in the Cu alloy core material is 0.05 to 1.2 mass%. Thus, the same effect as the case of containing the above-mentioned Ni, Zn, Rh, In, Ir, Pt, Ga, and Ge can be obtained. In the bonding wire of the present invention, from the viewpoint of improving the bonding reliability of the ball joint in a high temperature environment (especially the performance in HTS above 175°C), the concentration of Pd contained in the Cu alloy core material is preferably 0.05 mass% or more, more preferably 0.1 mass% or more, 0.2 mass% or more, 0.3 mass% or more, 0.4 mass% or more, or 0.5 mass% or more. In addition, from the viewpoint of obtaining a good FAB shape, suppressing the hardening of the bonding wire, and suppressing the reduction of wedge bonding properties, the concentration of Pd contained in the Cu alloy core material is preferably 1.2 mass% or less, and more preferably 1.1 mass% or less. The bonding wire of the present invention can improve loop forming properties by containing Ni, Zn, Rh, In, Ir, Pt, Ga, Ge, and Pd in ​​the above-mentioned content range, that is, can reduce leaning that becomes a problem in high-density mounting. This is because the yield strength of the bonding wire is improved by containing these elements, and the deformation of the bonding wire can be suppressed. Furthermore, as a method for determining the concentration of Pd contained in the Cu alloy core material from the bonding wire product, for example, a method of exposing the cross section of the bonding wire and performing concentration analysis on the region of the Cu alloy core material; a method of performing concentration analysis on the region of the Cu alloy core material while removing from the surface of the bonding wire in the depth direction by sputtering or the like. For example, in the case where the Cu alloy core material includes a region with a Pd concentration gradient, a wire analysis is performed on the cross section of the bonding wire, and a concentration analysis is performed on the region without a Pd concentration gradient (that is, a region where the degree of change in Pd concentration in the depth direction is less than 10 mol% per 0.1 μm). The method of concentration analysis will be described later.

[0051] In addition, by containing Ni, Zn, Rh, In, Ir, Pt, Ga, Ge, and Pd in ​​the above-mentioned content range, the bonding wire of the present invention can further improve the bonding life of the ball joint in a high temperature and high humidity environment of 130°C and a relative humidity of 85%. It can be considered that when the bonding wire of the present invention also contains a specified amount of Ni, Zn, Rh, In, Ir, Pt, Ga, Ge, and Pd, there is a tendency that the formation of Cu9Al4 intermetallic compounds in the bonding part is further suppressed. When these elements are also contained, the interfacial tension between the Cu of the core material and the Pd of the coating layer is further reduced, and the Pd concentration at the ball bonding interface is more significantly manifested. Therefore, it is presumed that the effect of suppressing the mutual diffusion of Cu and Al brought about by the Pd concentrated layer is further enhanced, and as a result, the amount of Cu9Al4 that is easily corroded by the action of Cl can be greatly reduced, and the reliability of the ball joint in a high temperature and high humidity environment is further improved.

[0052] Preferably: The bonding wire of the present invention further contains at least one element selected from B, P, Mg, Ca, and La, and the concentration of the element is 1 to 100 mass ppm relative to the entire wire. As a result, the crushed shape of the ball joint required for high-density mounting, that is, the roundness of the ball joint shape can be improved. It can be considered that this is because the addition of the above elements can make the crystal grain size of the ball finer and the deformation of the ball can be suppressed. From the viewpoint of improving the crushed shape of the ball joint, that is, improving the roundness of the ball joint shape, the concentration of the element is preferably 1 mass ppm or more, more preferably 2 mass ppm or more, 3 mass ppm or more, 4 mass ppm or more, or 5 mass ppm or more relative to the entire wire. From the viewpoint of suppressing the hardening of the ball and suppressing chip damage during ball bonding, the concentration of the element is preferably 100 mass ppm or less, more preferably 95 mass ppm or less, 90 mass ppm or less, 85 mass ppm or less, or 80 mass ppm or less relative to the entire wire. In the case where the bonding wire of the present invention contains a plurality of elements selected from B, P, Mg, Ca, and La, the total concentration of these elements is preferably 1 to 100 mass ppm relative to the entire wire. From the viewpoint of improving the crushed shape of the ball joint, that is, improving the roundness of the shape of the ball joint, the total concentration of the elements is preferably 1 mass ppm or more relative to the entire wire, and more preferably 2 mass ppm or more, 3 mass ppm or more, 4 mass ppm or more, or 5 mass ppm or more. In addition, from the viewpoint of suppressing the hardening of the ball and suppressing chip damage during ball bonding, the total concentration of the elements is preferably 90 mass ppm or less, 80 mass ppm or less, or 70 mass ppm or less relative to the entire wire.

[0053] For the concentration analysis of the Pd coating layer, the alloy skin layer containing Au and Pd, and the concentration analysis of Pd in ​​the Cu alloy core material, a method of performing analysis while removing from the surface of the bonding wire in the depth direction by sputtering or the like, or a method of exposing the wire cross section and performing line analysis, point analysis, etc. is effective. The analysis device used for these concentration analyses can be an Auger electron spectrometer equipped in a scanning electron microscope or a transmission electron microscope, an energy dispersive X-ray analysis device, an electron beam microanalyzer, etc. As a method for exposing the wire cross section, mechanical grinding, ion etching, etc. can be used. For the trace analysis of As, Te, Sn, Sb, Bi, Se, Ni, Zn, Rh, In, Ir, Pt, Ga, Ge, B, P, Mg, Ca, La, etc. in the bonding wire, an ICP emission spectrometer or an ICP mass spectrometer can be used to analyze the liquid obtained by dissolving the bonding wire with a strong acid, and the concentration of the elements contained in the bonding wire as a whole can be detected.

[0054] In a preferred embodiment of the present invention, in the measurement results obtained by measuring the crystal orientation of the bonding wire surface, the existence ratio of the crystal orientation <111> with an angle difference of less than 15 degrees relative to the length direction of the bonding wire is 30 to 100% in terms of area ratio. In this embodiment, the loop formability can be improved, that is, the straightness of the loop required in high-density installation can be improved, and the fluctuation of the loop height can be reduced. This is because if the surface crystal orientation is consistent, the resistance to lateral deformation is enhanced, thereby suppressing lateral deformation, and thus poor tilting can be suppressed. From the viewpoint of suppressing poor tilting, the existence ratio of the above-mentioned crystal orientation <111> is more preferably 35% or more in terms of area ratio, and further preferably 40% or more, 45% or more, 50% or more, or 55% or more.

[0055] (Manufacturing method)

[0056] Next, the manufacturing method of the bonding wire involved in the embodiment of the present invention is described. The bonding wire is obtained by manufacturing a Cu alloy for a core material, processing it into a thin wire, forming a Pd coating layer and an Au layer, and performing a heat treatment. Sometimes, after forming the Pd coating layer and the Au layer, wire drawing and heat treatment are performed again. The manufacturing method of the Cu alloy core material, the forming method of the Pd coating layer, the alloy skin layer containing Au and Pd, and the heat treatment method are described in detail.

[0057] The Cu alloy used for the core material is obtained by melting the raw material Cu and the added elements together and solidifying them. For melting, an arc heating furnace, a high-frequency heating furnace, a resistance heating furnace, etc. can be used. In order to prevent the mixing of gases such as O2 and H2 from the atmosphere, it is preferably melted in a vacuum atmosphere or an inert atmosphere such as Ar and N2.

[0058] The method of forming a Pd coating layer and an Au layer on the surface of a Cu alloy core material includes a plating method, a vapor deposition method, a melting method, etc. The plating method can be applied to any method of an electrolytic plating method and an electroless plating method. Electrolytic plating, which is called strike plating and flash plating, has a fast plating speed and good adhesion to the substrate. The solution used for electroless plating is classified into a displacement type and a reduction type. In the case of thin thickness, it is sufficient to use only a displacement type plating, but in the case of thick thickness, it is effective to implement a reduction type plating in stages after the displacement type plating.

[0059] In the vapor deposition method, physical adsorption such as sputtering, ion plating, and vacuum vapor deposition, and chemical adsorption such as plasma CVD can be used. All of them are dry methods, and there is no need to clean after forming the Pd coating layer or Au layer, and there is no need to worry about surface contamination during cleaning.

[0060] By performing heat treatment after forming the Pd coating layer and the Au layer, the Pd in ​​the Pd coating layer diffuses into the Au layer to form an alloy skin layer containing Au and Pd. Alternatively, the alloy skin layer containing Au and Pd may be coated from the beginning, rather than forming the alloy skin layer containing Au and Pd by heat treatment after forming the Au layer.

[0061] For the formation of the Pd coating layer and the alloy skin layer containing Au and Pd, any method of forming the Pd coating layer and the alloy skin layer containing Au and Pd after drawing the Pd coating layer to the final wire diameter and the method of forming the Pd coating layer and the alloy skin layer containing Au and Pd after drawing the Pd coating layer to the target wire diameter is effective. In the former case where the Pd coating layer and the alloy skin layer containing Au and Pd are formed at the final wire diameter, the manufacturing and quality control are very simple. In the latter case where the Pd coating layer and the alloy skin layer containing Au and Pd are combined with drawing, the adhesion with the Cu alloy core is improved. Specific examples of each formation method include: a method in which, for a Cu alloy core material of a final wire diameter, a Pd coating layer and an alloy skin layer comprising Au and Pd are formed while the wire is continuously swept through an electrolytic plating solution; or a method in which a rough Cu alloy core material is immersed in an electrolytic plating bath or an electroless plating bath to form a Pd coating layer and an alloy skin layer comprising Au and Pd, and then the wire is drawn to reach the final wire diameter; and the like.

[0062] After forming the Pd coating layer, the alloy skin layer comprising Au and Pd, sometimes heat treatment is performed. By heat treatment, atoms are diffused between the alloy skin layer comprising Au and Pd, the Pd coating layer, and the Cu alloy core material, and the adhesion strength is improved, so it is effective to suppress the peeling of the alloy skin layer comprising Au and Pd, the Pd coating layer in the processing, and improve the productivity. In order to prevent mixing with O2 from the atmosphere, preferably heat treatment is performed in an inert atmosphere such as vacuum atmosphere or Ar, N2.

[0063] As described above, by adjusting the conditions of the diffusion heat treatment and / or annealing heat treatment applied to the bonding wire, the Cu of the core material diffuses into the Pd coating layer and the surface alloy layer containing Au and Pd through grain boundary diffusion, etc., so that Cu can reach the outermost surface of the bonding wire so that Cu exists on the outermost surface. As a heat treatment for causing Cu to exist on the outermost surface, as described above, a heat treatment for forming an alloy skin layer containing Au and Pd can be used. When performing a heat treatment for forming an alloy skin layer, by selecting the heat treatment temperature and time, Cu can be present on the outermost surface or not. Furthermore, the Cu concentration on the outermost surface can also be adjusted to a specified range (for example, a range of 1 to 50 atomic %). Cu can also be diffused to the outermost surface by a heat treatment other than when the alloy skin layer is formed.

[0064] As described above, when As, Te, Sn, Sb, Bi, and Se are contained in the bonding wire, the effect of the present invention can be exerted regardless of whether these elements are contained in the Cu core material or are contained by coating the Cu core material or the wire surface. The same is true for Ni, Zn, Rh, In, Ir, Pt, Ga, Ge, B, P, Mg, Ca, and La.

[0065] As a method for adding the above-mentioned components, the simplest method is to add them to the starting material of the Cu alloy core material in advance. For example, high-purity copper and the above-mentioned component element raw materials are weighed as starting materials, and then heated and melted under high vacuum or in an inert atmosphere such as nitrogen and argon to make an ingot to which the above-mentioned components in the target concentration range are added as the starting material containing the above-mentioned component elements in the target concentration. Therefore, in a preferred embodiment, the Cu alloy core material of the bonding wire of the present invention contains at least one element selected from As, Te, Sn, Sb, Bi, and Se, so that the total concentration of the above elements is 0.1 to 100 mass ppm relative to the entire wire, and Sn≤10 mass ppm, Sb≤10 mass ppm, and Bi≤1 mass ppm. The preferred numerical range of the total concentration is as described above. In another preferred embodiment, the Cu alloy core material of the bonding wire of the present invention contains at least one element selected from Ni, Zn, Rh, In, Ir, Pt, Ga, and Ge, so that the total concentration of the above elements is 0.011 to 1.2 mass % relative to the entire wire. The preferred numerical range of the concentration is as described above. In a preferred embodiment, the Cu purity of the Cu alloy core material is 3N or less (preferably 2N or less). From the perspective of bonding, there is a tendency for Cu bonding wires coated with Pd to use high-purity (4N or more) Cu core materials and avoid using low-purity Cu core materials. The bonding wire of the present invention containing specific elements is particularly suitable for the case where a Cu alloy core material with low Cu purity as described above is used, thereby achieving the bonding reliability of the ball joint in a high temperature and high humidity environment required by vehicle-mounted devices. In another preferred embodiment, the Cu alloy core material of the bonding wire of the present invention contains at least one element selected from B, P, Mg, Ca, and La, so that the concentration of the above elements relative to the entire wire is 1 to 100 mass ppm. The preferred numerical range of the concentration is as described above.

[0066] The above-mentioned components can also be contained by coating the surface of the wire with the above-mentioned components during the online manufacturing process. In this case, the coating step can be incorporated into any time point of the online manufacturing process, and can be repeatedly incorporated multiple times. It can be incorporated into multiple processes. It can be added to the Cu surface before Pd coating, it can be added to the Pd surface after Pd coating, it can be added to the Au surface after Au coating, and it can also be incorporated into each coating process. As a coating method, it can be from (1) aqueous solution Select from (2) plating method (wet method) and (3) vapor deposition method (dry method).

[0067] In aqueous solution In the case of the method, firstly, a water-soluble compound containing the above-mentioned component elements is used to prepare an aqueous solution of appropriate concentration. In this way, the above-mentioned components can be incorporated into the wire material. The coating method can be incorporated into any time point of the wire manufacturing process, and can be repeatedly incorporated multiple times. It can be incorporated into multiple processes. It can be added to the Cu surface before Pd coating, it can be added to the Pd surface after Pd coating, it can be added to the Au surface after Au coating, and it can also be incorporated into each coating process.

[0068] When using a plating method (wet type), the plating method can apply any method in the electrolytic plating method and the electroless plating method. In the electrolytic plating method, in addition to the usual electrolytic plating, a plating method called flash plating with a fast plating speed and good adhesion to the substrate can also be applied. The solution used for electroless plating has a displacement type and a reduction type. Generally speaking, displacement plating can be applied when the coating thickness is thin, and reduction plating can be applied when the coating thickness is thick, but either can be applied, selected according to the concentration you want to add, and adjust the plating solution concentration and time. Both the electrolytic plating method and the electroless plating method can be incorporated into any time point of the online manufacturing process, and can be repeatedly incorporated many times. It can be incorporated into multiple processes. It can be added to the Cu surface before Pd coating, it can be added to the Pd surface after Pd coating, it can be added to the Au surface after Au coating, and it can also be incorporated into each coating process.

[0069] The evaporation method (dry method) includes sputtering, ion plating, vacuum evaporation, plasma CVD, etc. Since it is a dry method, no pretreatment or post-treatment is required, and there is no need to worry about contamination, which is an advantage. Generally speaking, the evaporation method has the problem of slow addition speed of the target element, but the addition concentration of the above-mentioned component elements is relatively low, so it is one of the methods suitable for the purpose of the present invention.

[0070] Each vapor deposition method can be incorporated into any time point of the online manufacturing process, can be repeatedly incorporated multiple times, can be incorporated into multiple processes, can be added to the Cu surface before Pd coating, can be added to the Pd surface after Pd coating, can be added to the Au surface after Au coating, and can be incorporated into each coating process.

[0071] The method of making the existence ratio of the crystal orientation <111> with an angle difference of 15 degrees or less with respect to the longitudinal direction of the bonding wire obtained when measuring the crystal orientation of the bonding wire surface to be 30 to 100% by area ratio is as follows. That is, by increasing the processing rate after the formation of the Pd coating layer or after the formation of the Pd coating layer and the Au skin layer, a directional texture (a texture with a uniform crystal orientation in the wire drawing direction) on the wire surface can be developed. Specifically, by making the processing rate after the formation of the Pd coating layer or after the formation of the Pd coating layer and the Au skin layer to be 90% or more, the existence ratio of the crystal orientation <111> with an angle difference of 15 degrees or less with respect to the longitudinal direction of the bonding wire obtained when measuring the crystal orientation of the bonding wire surface can be made to be 30% or more by area ratio. Here, it is expressed as "processing rate (%) = (wire cross-sectional area before processing - wire cross-sectional area after processing) / wire cross-sectional area before processing × 100".

[0072] When measuring the crystal orientation of the wire surface, the electron backscattered diffraction method (EBSD) is preferably used. The EBSD method has the characteristics of being able to observe the crystal orientation of the observation surface and to illustrate the angle difference of the crystal orientation between adjacent measurement points. Even for a thin wire such as a bonding wire, the crystal orientation can be observed relatively easily and with high precision.

[0073] The present invention is not limited to the above-described embodiments, and can be appropriately modified within the scope of the gist of the present invention.

[0074] Example

[0075] Hereinafter, the bonding wire according to the embodiment of the present invention will be described in detail while showing examples.

[0076] (sample)

[0077] First, the method for preparing the sample is described. The raw material of the core material, Cu, has a purity of 99.99% by mass or more, and the remainder is composed of inevitable impurities. As, Te, Sn, Sb, Bi, Se, Ni, Zn, Rh, In, Ir, Pt, Ga, Ge, Pd, B, P, Mg, Ca, and La have a purity of 99% by mass or more, and the remainder is composed of inevitable impurities. As, Te, Sn, Sb, Bi, Se, Ni, Zn, Rh, In, Ir, Pt, Ga, Ge, Pd, B, P, Mg, Ca, and La, which are elements added to the core material, are blended so that the composition of the wire or the core material becomes the target composition. Regarding the addition of As, Te, Sn, Sb, Bi, Se, Ni, Zn, Rh, In, Ir, Pt, Ga, Ge, Pd, B, P, Mg, Ca, and La, the single elements may be used for blending. However, in the case of elements with high melting points as single elements and / or in extremely small amounts, a Cu master alloy containing the added elements may be prepared in advance and then blended so as to achieve the target addition amount.

[0078] The core Cu alloy is manufactured by the following process, that is, the raw material is loaded into a cylindrical carbon crucible processed into a diameter of φ3 to 6 mm, and the raw material is heated to 1090 to 1300°C in a vacuum or in an inert atmosphere such as N2, Ar gas, etc. using a high-frequency furnace to melt it, and then the furnace is cooled. The obtained φ3 to 6 mm alloy is drawn, and after being processed to φ0.9 to 1.2 mm, a drawing die is used to continuously draw the wire, thereby producing a φ300 to 600 μm wire. A commercially available lubricating liquid is used in the wire drawing, and the wire drawing speed is set to 20 to 150 m / min. In order to remove the oxide film on the surface of the wire, the pickling treatment is carried out using hydrochloric acid, and then a Pd coating layer with a thickness of 1 to 15 μm is formed in a manner that covers the entire surface of the core Cu alloy. Furthermore, a portion of the wire forms an alloy skin layer containing Au and Pd with a thickness of 0.05 to 1.5 μm on the Pd coating. The electrolytic plating method is used to form the Pd coating layer and the alloy skin layer containing Au and Pd. The plating solution used is a commercially available semiconductor plating solution. Then, the wire is processed to a diameter of 20μm by repeatedly performing heat treatment at 200-500°C and wire drawing. After processing, heat treatment is performed while circulating N2 or Ar gas so that the final elongation at break becomes about 5-15%. The heat treatment method is to continuously sweep the wire while circulating N2 or Ar gas. The wire feeding speed is 20-200m / min, the heat treatment temperature is 200-600°C, and the heat treatment time is set to 0.2-1.0 seconds.

[0079] By adjusting the processing rate after the Pd coating layer is formed or after the Pd coating layer and the alloy skin layer containing Au and Pd are formed, the existence ratio (area ratio) of the crystal orientation <111> with an angle difference of less than 15 degrees relative to the length direction of the bonding wire obtained when measuring the crystal orientation of the bonding wire surface is adjusted.

[0080] The concentration analysis of the Pd coating layer and the alloy skin layer containing Au and Pd was performed by performing Auger electron spectroscopy while cutting from the surface of the bonding wire in the depth direction by sputtering, etc. The thickness of the Pd coating layer and the thickness of the alloy skin layer containing Au and Pd were obtained from the obtained concentration profile in the depth direction.

[0081] In Examples 93 to 98 of the present invention described in Table 1-5 below, the core material uses Cu with a purity of 99.99% by mass or more, and As, Te, Sn, Sb, Bi, and Se are coated on the surface of the wire by electroplating during the wire manufacturing process, thereby containing these elements. Therefore, a "Method of Adding Components" column is provided in Table 1-5, and in Examples 99 to 109 of the present invention, it is described as "coating layer". In all of Tables 1-1 to 1-4, and in the examples described as "core material" in the "Method of Adding Components" column of Table 1-5, As, Te, Sn, Sb, Bi, and Se are contained in the core material.

[0082] In the examples 99 to 109 of the present invention and the comparative examples 13 and 14 described in the following Table 1-5, Cu is present on the outermost surface of the bonding wire. Therefore, a column "Cu concentration on the wire surface" is provided in Table 1-5, which records the results obtained by measuring the surface of the bonding wire using an Auger electron spectrometer. By selecting the heat treatment temperature and time of the bonding wire, the outermost surface contains a predetermined concentration of Cu. For all of Tables 1-1 to 1-4, and the examples where the "Cu concentration on the wire surface" column in Table 1-5 is blank, the heat treatment conditions are set so that Cu does not exist on the outermost surface, and Cu is not detected even when an Auger electron spectrometer is used.

[0083] The structures of the samples prepared by the above-mentioned steps are shown in Tables 1-1 to 1-5.

[0084]

[0085]

[0086]

[0087]

[0088]

[0089] (Evaluation method)

[0090] The crystal structure was evaluated by using the wire surface as the observation surface. Electron backscattered diffraction (EBSD) was used as the evaluation method. The EBSD method has the characteristics of being able to observe the crystal orientation of the observation surface and to illustrate the angle difference of the crystal orientation between adjacent measurement points. Even for thin wires such as bonding wires, the crystal orientation can be observed relatively easily and with high precision.

[0091] When the EBSD method is applied to a curved surface such as a wire surface, it is necessary to pay attention. If a part with a large curvature is measured, it is difficult to perform a high-precision measurement. However, by fixing the bonding wire to be measured in a straight line on a plane and measuring the flat part near the center of the bonding wire, a high-precision measurement can be performed. Specifically, the measurement area can be set as follows. The circumferential dimension is set to less than 50% of the wire diameter with the center of the wire length direction as the axis, and the dimension in the wire length direction is set to less than 100μm. It is preferred to set the circumferential dimension to less than 40% of the wire diameter and the dimension in the wire length direction to less than 40μm. If so, the measurement efficiency can be improved due to shortening the measurement time. In order to further improve the accuracy, it is preferred to measure more than 3 places to obtain average information that takes into account fluctuations. It is better to keep the measurement site at a distance of more than 1mm so that it is not close.

[0092] The surface <111> orientation ratio is obtained by taking the total crystal orientations that can be determined using dedicated software (e.g., OIM analysis manufactured by TSL Solutions) as the parent group and calculating the existence ratio (area ratio) of the crystal orientation <111> having an angle difference of 15 degrees or less with respect to the length direction of the bonding line.

[0093] The bonding reliability of ball joints in a high temperature and high humidity environment or a high temperature environment is determined by making samples for bonding reliability evaluation, performing HAST and HTS evaluations, and judging the bonding life of the ball joints in each test. The samples for bonding reliability evaluation are electrodes formed by forming a 0.8μm thick Al-1.0%Si-0.5%Cu alloy film on a Si substrate on a general metal frame, ball bonding using a commercially available wire bonding machine, and sealing using a commercially available epoxy resin. The balls are formed while N2+5%H2 gas is flowing at a flow rate of 0.4 to 0.6L / min, and their size is set in the range of φ33 to 34μm.

[0094] For HAST evaluation, an unsaturated pressure cooker steam tester was used to expose the prepared samples for joint reliability evaluation to a high temperature and high humidity environment at a temperature of 130°C and a relative humidity of 85%, and a bias voltage of 5 V was applied. The joint life of the ball joint was set to a time when the shear strength value of the ball joint was 1 / 2 of the initial shear strength by performing a shear test on the ball joint every 48 hours. The shear test after the high temperature and high humidity test was performed after the resin was removed by acid treatment to expose the ball joint.

[0095] The shear tester for HAST evaluation uses a tester made by DAGE. The shear strength value adopts the average value of the measured values ​​of 10 randomly selected positions of the ball joint. In the above evaluation, if the joint life is less than 96 hours, it is judged to have practical problems and marked with ×, if it is more than 96 hours and less than 144 hours, it is judged to be practical but slightly problematic and marked with △, if it is more than 144 hours and less than 288 hours, it is judged to have no practical problems and marked with ○, if it is more than 288 hours and less than 384 hours, it is judged to be excellent and marked with ◎, if it is more than 384 hours, it is judged to be particularly excellent and marked with ◎◎, all of which are recorded in the "HAST" column of Table 1.

[0096] For HTS evaluation, the samples prepared for joint reliability evaluation were exposed to a high temperature environment of 200°C using a high temperature thermostat. The joint life of the ball joint was set to the time when the shear strength value of the ball joint was 1 / 2 of the initial shear strength by performing a shear test of the ball joint every 500 hours. The shear test after the high temperature and high humidity test was performed after removing the resin by acid treatment to expose the ball joint.

[0097] The shear tester used in the HTS evaluation was a tester manufactured by DAGE. The shear strength value was the average value of the measured values ​​at 10 randomly selected ball joints. In the above evaluation, if the joint life is more than 500 hours and less than 1000 hours, it is judged to be practical but still requires improvement and is marked with △, if it is more than 1000 hours and less than 3000 hours, it is judged to be practical and has no problem and is marked with ○, and if it is more than 3000 hours, it is judged to be particularly excellent and is marked with ◎.

[0098] The evaluation of ball formation (FAB shape) is to observe the ball before joining to determine whether there are bubbles on the surface of the ball and whether the originally round ball is deformed. If any of the above phenomena occurs, it is judged as defective. Regarding the formation of the ball, in order to suppress oxidation in the melting process, N2 gas is blown at a flow rate of 0.5L / min. The size of the ball is set to 34μm. 50 balls are observed for 1 condition. SEM is used for observation. Regarding the evaluation of ball formation, if more than 5 defects occur, it is judged to be problematic and recorded as an × symbol; if there are 3 to 4 defects, it is practical but has slight problems, recorded as a △ symbol; if there are 1 to 2 defects, it is judged to be no problem and recorded as an ○ symbol; if there is no defect, it is judged to be excellent and recorded as a ◎ symbol, all of which are recorded in the "FAB shape" column of Table 1.

[0099] The evaluation of the wedge bonding in the wire bonding part is to make 1000 joints on the lead part of the lead frame and judge by the frequency of peeling of the bonding part. The lead frame uses a Fe-42 atomic % Ni alloy lead frame with a 1 to 3 μm Ag plating layer. In this evaluation, stricter bonding conditions than usual are assumed, and the stage temperature is set to 150°C, which is lower than the general set temperature range. In the above evaluation, if more than 11 defects occur, it is judged to have problems and recorded as × symbols; if the number of defects is 6 to 10, it is practical but slightly problematic and recorded as △ symbols; if the number of defects is 1 to 5, it is judged to have no problems and recorded as ○ symbols; if no defects occur, it is judged to be excellent and recorded as ◎ symbols, all of which are recorded in the "Wedge Bonding" column of Table 1.

[0100] The evaluation of the crush shape of the ball joint is to observe the joined ball joint from directly above and judge it based on its sphericity. The joining object uses an electrode with an Al-0.5% Cu alloy film with a thickness of 1.0μm formed on a Si substrate. An optical microscope was used for observation, and 200 places were observed for one condition. The elliptical shape with a large deviation from the sphere and the anisotropic deformation were judged as poor crush shape of the ball joint. In the above evaluation, if more than 6 defects occur, it is judged to be problematic and marked ×. If there are 4 to 5 defects, it is judged to be practical but slightly problematic and marked △. If there are 1 to 3 defects, it is judged to be no problem and marked ○. If all good roundness is obtained, it is judged to be particularly excellent and marked ◎. All are recorded in the "Crush Shape" column of Table 1.

[0101] [tilt]

[0102] For the lead frame used for evaluation, 100 wires were bonded with a loop length of 5 mm and a loop height of 0.5 mm. As an evaluation method, the wire upright part was observed from the horizontal direction of the chip, and the interval (tilt interval) when the interval between the vertical line passing through the center of the ball joint part and the wire upright part was the largest was used for evaluation. When the tilt interval is smaller than the wire diameter, the tilt is judged to be good. When the tilt interval is larger than the wire diameter, the tilt is judged to be poor because the upright part is tilted. 100 bonded wires were observed under an optical microscope, and the number of wires with poor tilt was counted. When more than 7 defects occurred, it was judged to be problematic and marked with ×. If there were 4 to 6 defects, it was judged to be practical but slightly problematic and marked with △. When there were 1 to 3 defects, it was judged to be no problem and marked with ○. When there were no defects, it was judged to be excellent and marked with ◎. All of them are recorded in the "Tilt" column of Table 1.

[0103] (Evaluation results)

[0104] The bonding wires of Examples 1 to 109 of the present invention have a Cu alloy core material and a Pd coating layer formed on the surface of the Cu alloy core material, and the bonding wire contains at least one element selected from As, Te, Sn, Sb, Bi, and Se, and the total concentration of the above elements relative to the entire wire is 0.1 to 100 mass ppm. It was confirmed that the bonding wires of Examples 1 to 109 of the present invention obtained ball joint reliability in the HAST test under a high temperature and high humidity environment of 130°C and 85% relative humidity.

[0105] On the other hand, in Comparative Examples 1, 2, 4 to 6, and 11 to 14, the above-mentioned element concentrations deviated from the lower limit, and the ball joint reliability was not obtained in the HAST test. In Comparative Examples 3, 7 to 10, the above-mentioned element concentrations deviated from the upper limit, and the FAB shape was poor. In Comparative Examples 1, 3, 5 to 10, the area ratio of the <111> crystal orientation deviated from the appropriate range of the present invention and was tilted to △.

[0106] Regarding the examples of the present invention further including an alloy skin layer composed of Au and Pd on the Pd coating layer, it was confirmed that excellent wedge bondability could be obtained by setting the thickness of the alloy skin layer composed of Au and Pd to 0.0005 to 0.050 μm.

[0107] Regarding Examples 27 to 92, 100, 102, and 104 to 109 of the present invention, it was confirmed that the bonding wire also contained at least one element selected from Ni, Zn, Rh, In, Ir, Pt, Ga, Ge, and Pd, and the concentrations of the above elements other than Pd were 0.011 to 1.2 mass % relative to the wire as a whole, and the concentration of Pd contained in the Cu alloy core material was 0.05 to 1.2 mass %, so that the high-temperature reliability of the ball joint in the HTS evaluation was good.

[0108] In some of Examples 28 to 92 of the present invention, the bonding wire further contains at least one element selected from B, P, Mg, Ca, and La, and the concentration of the above elements is 1 to 100 mass ppm relative to the entire wire, so that the FAB shape is good and the wedge bonding property is good.

[0109] Inventive Examples 99 to 109, the wires contain As, Te, Sn, Sb, Bi, and Se, and Cu exists on the outermost surface of the wires. Therefore, in Inventive Examples 99, 101, 103, 105, 106, 108, and 109, the HAST evaluation results are ◎◎ or ◎, and the effect of having Cu on the outermost surface is observed. Inventive Examples 100, 102, 104, and 107, the Cu purity of the wires is low to 2N or less, and the HAST evaluation results are all ◎◎, which are very good. On the other hand, a slight decrease in wedge bondability is observed in these Inventive Examples.

[0110] In Comparative Examples 13 and 14, the wire does not contain As, Te, Sn, Sb, Bi, and Se. On the other hand, Cu exists on the outermost surface of the wire. Therefore, not only the HAST evaluation is poor, the HTS evaluation result is also poor, the FAB shape and the crush shape are also poor, and the wedge bondability and inclination are also deteriorated.

Claims

1. A bonding wire for a semiconductor device, comprising a Cu alloy core material and a Pd coating layer formed on a surface of the Cu alloy core material, characterized in that: The bonding wire contains at least one element selected from As, Te, Sn, Sb, Bi, and Se, and the total concentration of the elements relative to the entire wire is 0.1 to 100 mass ppm, Sn ≤ 10 mass ppm, Sb ≤ 10 mass ppm, and Bi ≤ 1 mass ppm. The bonding wire further contains at least one element selected from Ni, Zn, Rh, In, Ir, Pt, Ga, and Ge, and the concentration of the element is 0.011 to 1.2% by mass relative to the entire wire. The thickness of the Pd coating layer is 0.015 to 0.150 μm. Cu exists on the outermost surface of the bonding wire.

2. The bonding wire for a semiconductor device according to claim 1, wherein The total concentration of at least one element selected from the group consisting of As, Te, Sn, Sb, Bi, and Se is 1 to 100 mass ppm with respect to the entire wire.

3. The bonding wire for a semiconductor device according to claim 1, wherein An alloy skin layer containing Au and Pd is further provided on the Pd coating layer.

4. The bonding wire for a semiconductor device according to claim 3, wherein: The thickness of the alloy skin layer containing Au and Pd is 0.0005-0.050 μm.

5. The bonding wire for a semiconductor device according to claim 1, wherein The Cu alloy core material contains Pd, and the concentration of Pd contained in the Cu alloy core material is 0.05 to 1.2 mass %.

6. The bonding wire for a semiconductor device according to claim 1, wherein The bonding wire further contains at least one element selected from the group consisting of B, P, Mg, Ca, and La, and the concentration of each of the elements is 1 to 100 ppm by mass based on the entire wire.

7. The bonding wire for a semiconductor device according to any one of claims 1 to 6, wherein: In the measurement results of the crystal orientation on the surface of the bonding wire, the existence ratio of the crystal orientation <111> having an angle difference of 15 degrees or less with respect to the longitudinal direction of the bonding wire is 30 to 100% by area ratio.

Citation Information

Patent Citations

  • Copper alloy wire for connecting semiconductor element

    JP1986048543A

  • Bonding wire and integrated circuit device using the same

    JP2005167020A

  • Gold-coated copper wire for ball bonding

    JP2012036490A

  • Bonding wire for semiconductor

    CN102422404A

  • Plated copper wire structure used for ultrasonic bonding

    CN104241237A